Tensions on the actin cytoskeleton and apical cell junctions in the C. elegans spermatheca are influenced by spermathecal anatomy, ovulation state and activation of myosin - Sadeghian, Fereshteh; Grooms, Noa W. F.; Chung, Samuel H.; Cram, Erin J. (Frontiers in Cell and Developmental Biology, 2024)
Cells generate mechanical forces mainly through myosin motor activity on the actin cytoskeleton. In C. elegans, actomyosin stress fibers drive contractility of the smooth muscle-like cells of the spermatheca, a distensible, tube-shaped tissue in the hermaphrodite reproductive system and the site of oocyte fertilization. Stretching of the spermathecal cells by oocyte entry triggers activation of the small GTPase Rho. In this study, we asked how forces are distributed in vivo using the spermatheca, and explored how this tissue responds to alterations in myosin activity. Using laser ablation, we show that the basal actomyosin fibers are under tension in the occupied spermatheca. Reducing actomyosin contractility by depletion of the phospholipase C-ε/PLC-1 or non-muscle myosin II/NMY-1, leads to distended spermathecae occupied by one or more embryos, but does not alter tension on the basal actomyosin fibers. This suggests that much of the tension on the basal actin fibers in the occupied spermatheca is due to the presence of the embryo. However, activating myosin through depletion of the Rho GAP SPV-1 increases tension on the actomyosin fibers, consistent with earlier studies showing Rho drives spermathecal contractility. On the inner surface of the spermathecal tube, tension on the apical junctions is decreased by depletion of PLC-1 and NMY-1. Surprisingly, when basal contractility is increased through SPV-1 depletion, the tension on apical junctions also decreases, with the most significant effect on the junctions aligned in perpendicular to the axis of the spermatheca. This suggests tension on the outer basal surface may compress the apical side, and suggests the three-dimensional shape of the spermatheca plays a role in force distribution and contractility during ovulation.